2008
DOI: 10.1088/1475-7516/2008/08/016
|View full text |Cite
|
Sign up to set email alerts
|

f(R) cosmology from Noether’s symmetry

Abstract: A general approach to find out exact cosmological solutions in f (R)-gravity is discussed. Instead of taking into account phenomenological models, we assume, as a physical criterium, the existence of Noether symmetries in the cosmological f (R) Lagrangian. As a result, the presence of such symmetries selects viable models and allow to solve the equations of motion. We discuss also the case in which no Noether charge is present but general criteria can be used to achieve solutions.PACS numbers: 04.50.+h, 95.36.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
218
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(221 citation statements)
references
References 61 publications
(110 reference statements)
3
218
0
Order By: Relevance
“…We mention here that this is an special class of solutions founded before in literature [61] (for the case of purely f (R, T ) = F (R) see [61]). The associated Noether charge reads:…”
Section: Noether Symmetry In F (R T ) Gravitymentioning
confidence: 89%
“…We mention here that this is an special class of solutions founded before in literature [61] (for the case of purely f (R, T ) = F (R) see [61]). The associated Noether charge reads:…”
Section: Noether Symmetry In F (R T ) Gravitymentioning
confidence: 89%
“…Earlier attempts to find the Noether symmetry for ( ) theory of gravity in vacuum and matter dominated era lead to ( ) ∝ 3/2 [6][7][8][9][10][11][12][13]. Such a form is not suitable to explain presently available cosmological data [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the process, it is possible to construct a point Lagrangian, and one can demand Noether symmetry to find a suitable form of ( ). Following this technique, several authors [6][7][8][9][10][11][12] have found ( ) ∝ 3/2 in the Robertson-Walker metric both in vacuum ( = = 0) and pressureless dust ( = 0). Although such a form of ( ) shows accelerating expansion in the matter dominated era ( = 0), nevertheless, early decelerating phase tracks as ∝ 1/2 in the matter dominated era instead of usual 2/3 and ∝ 4/3 in the radiation dominated era ( = /3) instead of usual 1/2 , creating problem in explaining structure formation [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are two kinds of Noether symmetry approach for cosmological studies in the literature : The first one is the so-called Noether symmetry approach in which the Lie derivative of a given Lagrangian vanishes, (Capozziello and de Ritis 1993;de Ritis et al 1990;Demianski et al 1 Sanyal and Modak 2001;Camci and Kucukakca 2007;Souza and Kremer 2008) and the second one is the so-called Noether gauge symmetry (NGS) approach Hussain et al 2011 We note that the Noether symmetry approach without gauge term allows one to choose the potential dynamically in the scalar-tensor gravity theory (Sanyal et al 2003), and very recently, the explicit form of the function f (R) (Capozziello and de Felice 2008;Vakili 2008). For this form of f (R), cosmological solutions of FRW metric can describe the accelerated period of the universe.…”
Section: Introductionmentioning
confidence: 99%